General practitioners' clinical expertise in managing suicidal young people: implications for continued education. Issue 5 (24th May 2017) - Michail, Maria; Tait, Lynda; Churchill, Dick
Abstract : Aim: To examine general practitioners' (GPs) clinical expertise in assessing, communicating with, and managing suicidal young people aged 14–25 to inform the development of an educational intervention for GPs on youth suicide prevention. Background: Suicide is the second leading cause of death for young people worldwide. GPs are ideally suited to facilitate early identification and assessment of suicide risk. However, GPs' levels of competence, knowledge, and attitudes towards suicidal young people have not yet been explored. Methods: A cross-sectional survey on GPs' levels of confidence in assessing and managing young people at risk of suicide; knowledge of risk factors and warning signs of suicide in young people; attitudes towards young suicidal people; and training preferences on managing suicide risk. Findings: Seventy GPs completed the survey (30 males). The majority of GPs reported high levels of confidence in assessing and managing suicidality in young people. Experienced GPs demonstrated high levels of knowledge of suicide risk factors in young people but low levels of knowledge of warning signs that might indicate heightened risk. Although 48% of GPs disagreed that maintaining compassionate care is difficult with those who deliberately self-harm, GPs perceived communication with young people to be difficult, with one-third reporting frustration in managing those at risk of suicide. A total of 75% of GPs said they would be interested in receiving further training on assessing and managing young people at risk of suicide. The study has important implications for providing specialist training to support GPs in assessing and managing youth suicide risk and facilitating attitudinal change. GP education on youth suicide risk assessment and management should promote a holistic understanding and assessment of risk and its individual, social and contextual influences in line with clinical recommendations to facilitate therapeutic engagement and communication with young people.